Sei sulla pagina 1di 133

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

 

• •

• •

• • • 360 m a 60 m a 60 m a •

• • • 360 m a 60 m a 60 m a •

360 ma

60 ma

60 ma

α

α

30

π

6

 

π

45

4

60

π

3

90

π

2

180

π

270

3π

2

360

2π

α = 360

2π α

α = 2π

360

α

r = 1 α B α

r = 1 α B α • α α • α α • α α

α α

α α

α α

α =

=

α

α

=

α

1 α 1

1 α 1

α

α = 0

α (−∞, +) α

= π +

2

F unzione

F unzione reciproca

Condizione esistenza

α

α =

1

α

α

= 0 (α

= π + )

α

α =

1

α

α

= 0 (α

= π

2

+ )

α

α = α α

α

= 0 (α

= π + )

0 1 π   0 2 π − 1 3 π 0 2 2 π

0 1 π   0 2 π − 1 3 π 0 2 2 π

0

1

π

 

0

2

π

1

3π

0

2

2π

1

0

0

π

 

1

2

π

0

3π

1

2

2π

0

0 0 π   2 π 0 3 π 2 2 π 0 ∃ p

0

0

π

 

2

π

0

3π

2

2π

0

p > 0 x k

f(x) = f(x + kp)

2π

π

k Z

α = (α + 2)

α = (α + 2)

α = (α + )

π , π [0, π] π , π

2

2

2

2

1 1 π

2

=

π

=

2

1 1 0 π

=

=

−∞ < < + π

2

< < π

2

= =

y = (1)

y = 0

y = (1) π

y =

2

y = (0)

y = 0

2 α + 2 α = 1

2 α + 2 α = 1 α = 30 ◦ = π 6 π 6
2 α + 2 α = 1 α = 30 ◦ = π 6 π 6

α = 30 = π

6

π

6

= 1

2

π 6

= 3

2

α

= 45 = π

4

π

4 =

π

4 =

2

2

2

2

α = 60 ◦ = π 6 π 3 π 3 = 1 2 =

α = 60 = π

6

π

3

π

3

= 1

2

= 3

2

2 α + 2 α = 1

α = α α

1

α

α = α α

α

= π +

2

• α = α α α = π + kπ 2

α

= π +

α =

1

= π +

α

α

2

α =

α

= π +

(α + β) = α β α β

(α β) = α β + α β

(α + β) = α β + α β

(α β) = α β α β

(α + β) =

(α β) =

α + β

1 α β

α β

1 + α β

(2α) = 1 2 2 α = 2 2 α 1

(2α) = 2 α α

(2α) =

2 α

1 2 α

α

2

= ± 1 + α

2

α

2

α

2

= ± 1 α

2

= ± 1 α

1 + α

t = α

2

α = 1 1 + t t 2 2

α =

2t

1 + t 2

p + q = 2

p + q p q

2

2

p q = 2 p + q p q

2

2

p + q = 2 p + q p q

2

2

p q = 2

p + q p q

2

2

α β

2 k = 0, 1, 2,

α

+ β = π + 2

2

2 k = 0, 1, 2,

α + β = π + 2

2 k = 0, 1, 1,

α = β

⇐⇒

β = α

π 2 − α = α π 2 − α = α π 2 −

π

2

α = α

π

2

α = α

π

2

α = α

π

2

α = α

( π − α ) = α ( π − α ) = − α

(π α) = α

(π α) = α

(π α) = α

(π α) = α

( − α ) = − α ( − α ) = α ( −

(α) = α

(α) = α

(α) = α

(α) = α

π + α = α 2 π + α = − α 2 π +

π + α = α

2

π + α = α

2

π + α = α

2

π + α = α

2

( π + α ) = − α ( π + α ) = −

(π + α) = α

(π + α) = α

(π + α) = α

(π + α) = α

3π 2

3 π 2 3 π + α = − α 2 3 π + α =

3π + α = α

2

3π + α = α

2

3π + α = α

2

3π + α = α

2

= ,

= ,

= ,

, ,

R

= =

1 1 1 1

< 1 > 1

< 1 > 1)

=

R

= 5 π + 2 k π 1 • 2 π 2 = 0 4
= 5 π + 2 k π
1
• 2
π
2 = 0
4 −
• = 5 4
5 4 > 1

1 2 = 0

=

= π + 2 k π ;

6

6

2 2 + 5 4 = 0

2(1 2 ) + 5 4 = 0

2 2 5 + 2

= 0

= 5 ±

25 16

  = 2

1

4

=

= ± π

=

2

3

+ 2

+ + = 0 ,

, ,

R ,

= 0

= 0

= 0

3 = 0

= π

2

+

3

= 3 = 0

3

=

= 3

=

= π +

= 0

 
 

+ 1 = 0

 

= π + 2

 

α = 1 1 + t t 2 2

;

α =

;

t = α

 

2t t 2 1 +

2

2t t 2 + 1 t

1 + t

1 +

2

2 1 = 2t + 1 t 2 1 t 2 = 2t 2 + 2t = 0

 

=⇒ −2t(t 1)

= 0

=

t = 0

t = 1

 

 

 
 

=

2

= 0

2

= 1

 

=

=

= π +

 
 

2

2

4

 

=

= 2

= π + 2

2

 
 

3 + = 3

  3 + = 3

2 + 2 = 1

= =

3X + Y = 3

  X 2 + Y 2 = 1



 

= 1 =

= 0 =

1

2

= 2

= √ 3   X 2 + Y 2 = 1 → → → 

= 2 =

= 3

=

→  = 2 = = √ 3 = → = π + 2 kπ 3
→  = 2 = = √ 3 = → = π + 2 kπ 3

= π + 2

3

2 +

+ 2 = 0 ,

, ,

R ,

= 0

= 0

= 0

= 0

2 3 = 0

( 3 = 0)

 

= 0

=

=

3 = 0

=

= 3

=

= π +

3

= 0

= 0

2 (1 + 3) + 3 2 = 0

2 (1 + 3) + 3 = 0

x = (1 + 3) ±

(1 + 3) 2 4 3

2

4

3

= 1

=

= π +

= 3

=

= π +

π  = 3   = 2 − 1     =
π
=
3
 = 2 − 1
 
= 0
= 0
  
= 0
=⇒
= 0
 
2 − 1 = 0
= 1
2
= π
 
= π
3
3
= √ 3
2
2
 
= √ 3 + 2
2 − 1 = √ 3
2
4
0, π
3
1
2 ≤ ≤ √ 3 + 2
4

= 2 1

0

=

=

 

= 3

2 + 1 = 0